Dinamika Kebijakan Pangan Orde Baru: Otonomi Negara vs Pasar Global - Fatih Gama Abisono (Jurnal Ilmu Sosial dan Ilmu Politik, 2002)
Food policy is not independently designed, as it is structurally hound. State's autonomy is even more questionable as globalized-politicaleconomic structure gaining stronger grip in Indonesia, especially after monetary crisis at the end of New Order period.